Neonate with meroacrania: radiological findings and review of the literature - Yildirim, Hanefi; Koc, Mustafa; Kurt, Nese; Artas, Hakan; Aygun, Denizmen (Aves, 2009)
Acrania is a developmental abnormality characterized by a partial or complete absence of calvaria with complete but abnormal development of brain tissue. Acrania is a relatively common malformation and affects about 1 in 1000 newborns. Meroacrania refers to absence of the cranium with the exception of the occipital bone. Brain stem and cerebellum develop normally, but cerebral parenchyma tissue is covered with a thin membrane and severely dysmorphic supratentorial brain is also seen. The other system findings are normal. Magnetic resonance imaging findings of one neonate with meroacrania have been reported in medical literature. Other radiographic and computed tomography findings have not yet been reported. We report a female neonate with meroacrania with discussion of etiology, pathogenesis, radiological findings, and differential diagnosis.
Keywords: meroacrania; x-ray; computed tomography; magnetic resonance imaging